Unrealized concepts of masked alkylidenes in (PNP)FeXY systems and alternative approaches to LnXmFe(IV)=CHR. (1st May 2020) - George, Gregory M.; Wolczanski, Peter T.; MacMillan, Samantha N.; Cundari, Thomas R.
Graphical abstract: Various PNP chelates were employed in (PNP)FeX(Y) (X(Y) = halide, alkyl) complexes designed to generate (PNP)CRR′FeXY "masked alkylidenes", but this and alternative approaches failed to generate olefin metathesis active Fe(IV) alkylidenes, prompting consideration of orbital requirements. Abstract: Treatment of PNP ligands with iron(II) halides yielded pseudo tetrahedral (Ph2 PCH2 )2 NRFeX2 (R″ = t Bu, 1a -X; Me, 1b -X) and ( i Bu2 PCH2 )2 NR″FeX2 (R″ = t Bu, 2a -X; Me, 2b -X) complexes, which could be mono- and dialkylated to afford various (Ph2 PCH2 )2 NR″FeCl(R) (R″ = t Bu, 3a -R; Me, 3b -R), ( i Bu2 PCH2 )2 NR″FeCl(R) (R″ = t Bu, 4a -R; Me, 4b -R), (Ph2 PCH2 )2 N t BuFe( neo Pe)2 (5a - neo Pe) and ( i Bu2 PCH2 )2 N t BuFe(1-nor)2 (6a -nor). All of the complexes were high spin ( S = 2), and structural studies of (Ph2 PCH2 )2 NMeFeCl2 (1b -Cl), ( i Bu2 PCH2 )2 N t BuFeCl2 (2a -Cl), and ( i Bu2 PCH2 )2 N t BuFeCl(1-nor) (4a -nor), revealed chair conformations for the PNP ligands, which were calculated to have modest barriers to boat configurations via twist-boats as calculational minima. Attempts to convert these complexes to zwitterionic NCRR′Fe-containing species as "masked alkylidenes" failed to materialize. Alternative approaches involving structurally characterized diamagnetic ( i Bu2 PCH2 )2 N t Bu(CO)2 FeCl(CO neo Pe) (8 ), the carbonylation product of 4a - neo Pe, and low-valent (Ph2 PCH2 CH2 )2 N t BuFe((H2 C=CHSiMe2 )2 O) (9 ) also failed. An analysis of orbital energies and overlap is given for alkylidenes. Covalence is identified as a crucial feature necessary for the alkylidene to metalacyclobutane transformation in metathesis.